Aspekte der Dopaminbehandlung im hirntoten Organspender bei Nierentransplantation - Höger, Simone; Justus Liebig University Giessen (My University, 2007)
Transplantatnieren von hirntoten Spendern haben eine wesentlich schlechtere Prognose als Nieren von lebenden Spendern. Schon während des Hirntodes kommt es in der Spenderniere zu einer verstärkten Aktivierung des Immunsystems und somit zu einer erhöhten Immunogenität des Transplantats. Dies wirkt sich negativ auf das Transplantatüberleben aus. Aufgrund hämodynamischer Instabilität müssen hirntote Patienten häufig mit Katecholaminen behandelt werden. In zwei unabhängigen retrospektiven klinischen Studien konnte gezeigt werden, dass Dopaminbehandlung von hirntoten Organspendern die Nierenfunktion und das Langzeittransplantatüberleben im Transplantatempfänger verbessert. Im Tiermodell konnte außerdem gezeigt werden, dass Dopaminbehandlung von hirntoten Ratten die renale Inflammation in der Spenderniere dosisabhängig reduziert.Im Rahmen dieser Arbeit wurde mittels einer Zeit-Wirkungs-Analyse ermittelt, ob eine Dopaminspendervorbehandlung auch dann noch protektive Effekte ausübt, wenn sie nicht über die gesamte Hirntoddauer erfolgt. Desweiteren wurden mögliche Wirkmechanismen, die zu den protektiven Effekten der Dopaminspendervorbehandlung beitragen können, untersucht. Zuletzt wurde in einem allogenen Transplantationsmodell untersucht, inwieweit sich eine Dopaminvorbehandlung über den optimalen Behandlungszeitraum im hirntoten Spendertier auf die akute Abstoßung im Empfängertier auswirken kann.

Brain death is a major cause of pre-transplantation injury of allografts. According to the damage hypothesis, pre-transplantation injury would have an important impact on transplantation outcome. Indeed allografts retrieved from brain dead donors show a decreased long-term survival compared to those from living donors. In two independent retrospective clinical studies, we could show a beneficial effect of donor dopamine treatment on graft function and long-term renal allograft survival. In addition, we have recently demonstrated in an animal model that dopamine treatment during brain death reduces monocyte infiltration in renal grafts. In the present study, we investigated the anti-inflammatory response mediated by dopamine in kidneys of brain-dead donor rats with regard to time-dependency and possible underlying mechanisms. Moreover, we investigated the influence of brain-dead donor treatment with dopamine on acute rejection episodes after allogeneic kidney transplantation.Brain death was induced in Fisher donor rats. Duration of brain death was in all experiments 6 hrs. Apneic animals were mechanically ventilated, and dopamine (10müg/kg/min) was given for 6, 3 respectively 1 hrs from the onset of brain death or 1 respectively 3hrs before renal explantation. Ventilated (6 hrs), non brain-dead animals served as controls. Peripheral blood for FACS analysis was collected before and 6 hrs after brain death from brain-dead controls and dopamine treated animals. Other brain-dead animals received either blood pressure lowering, alpha/beta-adrenergic antagonists, or dopaminergic blockers for investigating hemodynamic and non-hemodynamic mechanisms of dopamine. Immunohistochemistry and RNA analysis were performed in retrieved kidneys. In the transplantation model, explanted kidneys were stored for 24 hrs at 4°C in University of Wisconsin solution and transplanted into Lewis rats. Whereas in untreated brain-dead animals hypotension occurred, dopamine treatment during brain death completely normalized blood pressure. Concomitantly, the number of infiltrating ED-1+/MHC class II+ monocytes was reduced. Time response experiments revealed that 3 hrs of dopamine treatment from the onset of brain death was sufficient to reduce infiltration and thus, to reduce the graft immunogenicity. Although blood pressure was still improved when dopamine was applied during the last 3 hrs of brain death, this did not influence monocyte infiltration. We therefore concluded that the effect of dopamine is only partly depending upon hemodynamic changes. The beneficial effect of dopamine on infiltration was abrogated by blood pressure lowering and both dopaminergic and alpha/beta-adrenergic receptor blockers. Moreover application of the D-receptor agonist pergolide inhibited monocyte infiltration in kidneys of brain dead donors. Therefore we suggest that some of the beneficial effects are affected by dopaminergic or adrenergic receptors. Dopamine downregulated gene-expression of HO-1 (hemeoxygenase-1) in renal tissue of brain-dead rats compared to untreated controls. Surface molecules of inflammatory cells in the peripheral blood were not influenced by brain death independent of dopamine treatment. Therefore brain death seems to influence infiltrating cells more than inflammatory cells in the peripheral blood. Brain-dead donor pre-treatment with dopamine had no protective effects on acute rejection episodes in this model of allogeneic kidney transplantation.These findings confirm and expand findings from two independent retrospective clinical studies and may help to improve the treatment of cadaveric kidney donors. A prospective randomized clinical trial studying the effects of dopamine treatment cadaveric renal transplantation is currently under progress.
Keywords: ddc:630